Trastorno de ansiedad y el ambiente familiar de los pacientes con Insuficiencia Renal Crónica del Centro de Hemodiálisis Unidad Dialecon Quevedo Da Vida - Macay Vera, Steven Daniel (2017)
Hemodialysis is the treatment for patients with chronic kidney failure that has no cure which has to be performed for life and causing it has many repercussions both personally and in the family. Therefore, it must be taken into account in the therapeutic management to be applied. Objective: To determine the influence of anxiety disorder in the family environment of patients with chronic kidney failure at the Dialecon Quevedo Da Vida Unit Hemodialysis Center. Materials and methods: it was done through a cross-sectional descriptive quantitative study. Based on the topic, the questions to be asked of 88 relatives of the patients were determined. Conclusions: This is a synthesis of the most important data and analysis of its occurrence in the described situation. Interpretation involves all members, there is a need for interrelation, interpretation and evaluation of the data obtained in the study, to indicate the following: Problem; cause; the consequences of the problem and the people affected; possible future risk of continuation of the problem; Potential and resources detected in people and situations, including sources of information.